The effects of exchange rate volatility on agricultural crops export to various countries - ayat Karami; mansour Zibaei (پژوهشهای اقتصادی, 2008)
Since Iran is one of the most important countries in producing as well as exporting pistachio and dates Therefore, in this study after calculating exchange rate volatility using the criterion of standard deviation of exchange rate moving average, the effects of this volatility on the export supply of mentioned crops was investigated. Autoregressive distributed lag model, one of the co-integration analysis methods, was used to reach the aim. Export supply function of pistachio to German, Unit Kingdom and Italy and export supply of dates to German, Unit Kingdom and Turkey were estimated. The results indicated that exchange rate volatility has different effects on export of the crops to understudy countries. Therefore in relation to trade policies, the effect of exchange rate volatility on trade should be considered with respect to destined country.